Analysis and Evaluation of Environmental Management - MUKHTAROVA, Karlygash; TUREKULOVA, Dametken; LESBAYEVA, Gulnara; YESTURLIEVA, Aigul; SAIMAGAMBETOVA, Gaukhar (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018DO - 10.14505//jemt.v9.1(25).21, 2018)
Today, Kazakhstan has accumulated a huge amount of environmental, social and ecological problems that prevented the development of the country on a stable basis. The economic growth of the country is mainly due to rising prices for raw materials on world markets and the use of a significant amount of natural resources. At the root of many social and economic problems of the Republic of Kazakhstan is historically an imbalance when the country consumes resources disproportionately in comparison with their production.